Behavioural responses of southern mountain caribou to helicopter and skiing activities - Wilson, Steven F.; Wilmshurst, John F. (Rangifer, 2019)
Helicopter- and snowcat-supported backcountry skiing is a unique industry that is widespread throughout southern mountain caribou habitat in British Columbia. We analyzed standardized caribou encounter data collected by operators under an agreement between the BC government and Helicat Canada. Average reported encounter rates were low for helicopters (0.6%) and skiing groups (0.1%); however, encounters were likely underreported due to factors that affect caribou sightability. Although helicopters encountered caribou more frequently than skiing groups, caribou were detected from helicopters at greater distances than by skiers. We used Bayesian network models to assess the independent contribution of different factors to the behavioural response of caribou to encounters. Encounter distance was the most important factor in both helicopter and skiing models. Larger groups of caribou responded strongly to skiers but not to helicopters, although the independent effect of this factor was small in both models. Larger helicopters elicited stronger reactions from caribou than smaller machines and was responsible for 25% of the modelled variation in caribou response. Encounters with helicopters at distances of 100–500m had a 78% probability of eliciting a concerned-to-very-alarmedresponse from caribou, while skiers at a similar distance had a 60% probability of eliciting the same response. The probability of concerned-to-very-alarmed responses dropped to <20% at encounter distances of >1000 m. These results indicate that initial encounter distance is the key variable to manage risk to caribou of helicopter and skiing encounters. Ongoing feedback on the effectiveness of management practices is critical to ensure the continued viability of industries operating in caribou habitat.